The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4062/biomolther.2016.137
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Substance P Attenuates Mechanical Allodynia Following Nerve Injury by Regulating Neuropathic Pain-Related Factors

Abstract: This study aimed to investigate the analgesic effect of substance P (SP) in an animal model of neuropathic pain. An experimental model of neuropathic pain, the chronic constriction injury (CCI) model, was established using ICR mice. An intravenous (i.v.) injection of SP (1 nmole/kg) was administered to the mice to examine the analgesic effects of systemic SP on neuropathic pain. Behavioral testing and immunostaining was performed following treatment of the CCI model with SP. SP attenuated mechanical allodynia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…33 In NC model rats where substance P was injected, GFAP decreased as mechanical allodynia was mitigated; on the other hand, anti-inflammatory factors were actively expressed. 34 Moreover, 5-HT 2A has the ability to increase potassium chloride cotransporter type 2, thereby mediating motoneuronal inhibition and alleviating NP induced by spinal cord injury. 35 GABA B2, which plays a role in maintaining the analgesic function of opioid oxycodone, was reduced with nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…33 In NC model rats where substance P was injected, GFAP decreased as mechanical allodynia was mitigated; on the other hand, anti-inflammatory factors were actively expressed. 34 Moreover, 5-HT 2A has the ability to increase potassium chloride cotransporter type 2, thereby mediating motoneuronal inhibition and alleviating NP induced by spinal cord injury. 35 GABA B2, which plays a role in maintaining the analgesic function of opioid oxycodone, was reduced with nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…In 1980, Oehme et al suggested that SP produced naloxone-reversed analgesia in mice with high sensitivity to thermal stimulation but induced hyperalgesia in mice with low sensitivity to thermal stimulation [41]. In addition, SP has been found to effectively reduce neuropathic pain [42] and inflammatory pain [43]. To sum up, these studies demonstrated that SP can regulates opioid-dependent analgesic effects in distinct cell types, probably via different receptors.…”
Section: Sp-mediated Anti-nociceptionmentioning
confidence: 99%
“…SP might represent a good drug candidate for neuropathic pain management; however, further investigations should be performed to determine its exact mechanism of action. 23 Natural compounds have been investigated for the management of many diseases, and some of them may present therapeutic candidates for the development of new drugs to alleviate neuropathic pain.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…SP might represent a good drug candidate for neuropathic pain management; however, further investigations should be performed to determine its exact mechanism of action. 23 …”
Section: Preclinical Studiesmentioning
confidence: 99%